Muon study of the spin dynamics in the organic spin-peierls compound MEM(TCNQ)(2) - Lovett, B; Blundell, S; Jestadt, T; Pratt, F; Kurmoo, M; Tagaki, S; Hayes, W (Elsevier, 1999)
We report a muon spin relaxation study of the organic spin-Peierls system MEM(TCNQ)(2) over the temperature range 39 mK to 200 K. Our results show a crossover from Gaussian to exponential relaxation below the spin-Peierls transition temperature. We attribute this change to the effect of a dilute set of static electronic defect spins resulting from the majority of spins freezing into a non-magnetic spin singlet state.